Nanoscale hybrid multidimensional perovskites with alternating cations for high performance photovoltaic. (November 2019) - Gu, Hao; Liang, Chao; Xia, Yingdong; Wei, Qi; Liu, Tanghao; Yang, Yingguo; Hui, Wei; Chen, Haoran; Niu, Tingting; Chao, Lingfeng; Wu, Zhiheng; Xie, Xiaoji; et al.
Abstract: Two-dimensional (2D) metal-halide perovskites with alternating cations in the interlayer space (ACI) have demonstrated great potential in photovoltaics. The balance between stability and efficiency could be tailored by varying the distance between the inorganic slabs. However, the efficiencies are still low due to the low carrier mobility and random crystal orientation in the defective ACI films. Furthermore, how the ACI multidimensional perovskites assembled in the solution-processed film is still unclear. Herein, we demonstrated nanoscale hybrid multidimensional (GA)(MA)3 Pb3 I10 ACI (guanidinium = GA, methylammonium = MA) perovskite with vertically stacked microcrystals and preferential crystal orientation. In each microcrystal, the low-dimensional ACI are assembled within 3D perovskite nanoscale networks. Such nanoscale heterojunctions prompt ultrafast (~0.3 ps) charge carrier localization from ACI to 3D perovskite and the subsequent efficient charge carrier extraction from the 3D networks to the extraction layers. Based on optimized ACI films, record high-efficiency (>16%) and high-stability planar perovskite cells are achieved. Our results provide new insight into the crystal growth and carrier kinetics of the ACI perovskite solar cells. Graphical abstract: The ACI perovskite with micro-meter crystals are vertically stacked with preferential crystal orientation. In each microcrystal, the low-dimensional ACI perovskites are crystalized in the 3D perovskite nanoscale networks. Such nanoscale hybridization prompts ultrafast (0.3 ps) and efficient charge carrier localization from low-dimensional ACI perovskites to 3D perovskite and the subsequent fast and efficient charge carrier extraction from the 3D networks to the extraction layers. Based on the optimized ACI perovskite film, planar heterojunction PSC achieved a high PCE exceeding 16% and kept 80% of the initial value for over 2400 h. Image 1 Highlights: The perovskite micro-meter crystals are vertically stacked with preferential crystal orientation. The HRTEM confirms low-dimensional ACI perovskites are crystalized in the 3D perovskite nanoscale networks. The TA spectra revealed nanoscale hybridization prompts ultrafast and efficient charge carrier localization from low-dimensional ACI perovskites to 3D perovskite and ultrafast carrier collection. Based on the optimized ACI perovskite film, planar heterojunction PSC achieved a high PCE exceeding 16% and kept 80% of the initial value for over 2400 h.